Pengaruh Mutasi, Motivasi dan Lingkungan Kerja Terhadap Kinerja Pegawai Badan Pertanahan Nasional (BPN) Karanganyar - Wulandari, Niken Tri; Cahyani, Rusnandari Retno; Prihatini, Prima (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
This study aims to determine the effect of mutation, motivation and work environment on the performance of Karanganyar National Land Agency (BPN) employees. This research is descriptive research using quantitative methods. The population in this study were employees of the Karanganyar National Land Agency (BPN), the sample used was 118 respondents. The results of this study indicate that the value of Fhitung> Ftabel = 11.978> 2.68 with a significance value of 0.000 <0.05, meaning that mutation, motivation and work environment simultaneously and significantly affect the performance of employees of the National Land Agency (BPN) Karanganyar. Among the three variables above, mutation and the work environment partially have no significant effect on employee performance, while motivation partially has a significant effect on the performance of employees of the Karanganyar National Land Agency (BPN). It is known that the calculation of the coefficient of determination R Square value obtained is 0.240, meaning that the independent variable in explaining the dependent variable is 24% while the remaining 76% is influenced by other factors not examined in this study.